White light-emitting diode daubed via CaSc2O4:Ho3+/Yb3+ nanocrystal sheets enclosed using SiO2 - Tung, Ha Thanh; Nguyen Thi, Dieu An (Bulletin of Electrical Engineering and Informatics, 2024)
Our investigation assesses the downshifting (DS), periodicity up-transmutation as well as internal light consistency from phosphor samples of CaSc2O4 incorporated with Ho3+/Yb3+ along with up-conversion from CaY2O4 incorporated with Ho3+/Yb3+. These samples are created via precursor antecedent compound technique. The generation for the crystalline samples having orthorhombic stage is validated by the X-ray powder diffraction. The dispersal reflectance spectra exhibit several lines within the zones of ultraviolet–visible–near infrared (UV-vis-NIR), resulting from the ions of Ho3+ as well as Yb3+. The optical band gap (Eg) results reach 5.69 and 5.58 eV, corresponding to CaSc2O4:Ho3+/Yb3+ and CaY2O4:Ho3+/Yb3+. The CaSc2O4:Ho3+/Yb3+ samples exhibit potent downshifting discharge in green hue when excited under 454 nm. CaSc2O4:Ho3+/Yb3+, as well as CaY2O4:Ho3+/Yb3+, exhibit potent discharges in green hue as well as near-infrared up-transmutation discharges in faint blue and red hues when excited under 980 nm. The spectrum hue clarity -Sgr – for CaSc2O4:Ho3+(1%)/Yb3+(5%) reaches 0.78. The disparity in pumping force yields internal light consistency for said sample with the green discharge, being nonexistent in the CaY2O4:Ho3+(1%)/Yb3+(5%) sample. As such, CaSc2O4:Ho3+/Yb3+ may prove useful when applied to up-transmutation apparatuses.